Evaluation of different procedures for fertilization and larvae production in Hediste diversicolor (O.F. Müller, 1776) (Nereididae, Polychaeta). (13th January 2018) - Nesto, Nicoletta; Simonini, Roberto; Prevedelli, Daniela; Da Ros, Luisa
Abstract: Different experimental trials were performed to clarify some aspects of the biology of the polychaete Hediste diversicolor (O.F. Müller, 1776) as a further step towards the development of appropriate breeding protocols for indoor farming systems. In particular, the trials were addressed to evaluate the effectiveness of two fertilization conditions (in vitro and "natural‐like"); induce gamete spawning by exposing mature individuals to thermal shock or to tissue homogenates; estimate the density effects on larval growth and survival; and evaluate the most suitable parameters to be used as proxy for biomass assessment. The highest percentages of fertilized eggs and larvae were obtained by the in vitro fertilization condition. Mature organisms were induced to spawn by exposure to thermal shock although the spawned eggs revealed low rates of fertilization and hatching. The treatment with male tissue homogenates induced females to successful spawning, and the resulting eggs showed high fertilization and hatching rates. The density of larvae in the rearing phase had no effect on growth or on survival rates of juveniles. Finally, allometric evaluations showed that fresh weight and L3 length are the most reliable parameters to be used as proxy for biomass assessment of this species.